Effect of fluconazole prophylaxis on Candida fluconazole susceptibility in premature infants. (20th September 2018) - Autmizguine, Julie; Smith, P Brian; Prather, Kristi; Bendel, Catherine; Natarajan, Girija; Bidegain, Margarita; Kaufman, David A; Burchfield, David J; Ross, Ashley S; Pandit, Paresh; Schell, Wiley A; Gao, Jamie; et al.
Abstract: Objectives: Extremely premature infants are at high risk of developing invasive candidiasis; fluconazole prophylaxis is safe and effective for reducing invasive candidiasis in this population but further study is needed. We sought to better understand the effect of prophylactic fluconazole on a selection of fluconazole-resistant Candida species. Methods: We evaluated the susceptibility to fluconazole of Candida isolates from premature infants (<750 g birth weight) enrolled in a multicentre, randomized, placebo-controlled trial of fluconazole prophylaxis. Candida species were isolated through surveillance cultures at baseline (study day 0–7), period 1 (study day 8–28) and period 2 (study day 29–49). Fluconazole MICs were determined for all Candida isolates. Results: Three hundred and sixty-one infants received fluconazole ( n  =   188) or placebo ( n  =   173). After the baseline period, Candida colonization was significantly lower in the fluconazole group compared with placebo during periods 1 (5% versus 27%; P  <   0.001) and 2 (3% versus 27%; P  <   0.001). After the baseline period, two infants (1%) were colonized with at least one fluconazole-resistant Candida in each group. Median fluconazole MIC was similar in both treatment groups at baseline and period 1. However, in period 2, median MIC was higher in the fluconazole group compared with placebo (1.00 versus 0.50 mg/L, P  =   0.01). There was no emergence of resistance observed and no patients developed invasive candidiasis with a resistant Candida isolate. Conclusions: Fluconazole prophylaxis decreased Candida albicans and 'non- albicans ' Candida colonization and was associated with a slightly higher fluconazole MIC for colonizing Candida isolates.